2022
DOI: 10.3390/cells11132021
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Sequencing: Astrocyte and Microglial Heterogeneity in Health and Disease

Abstract: Astrocytes and microglia are non-neuronal cells that maintain homeostasis within the central nervous system via their capacity to regulate neuronal transmission and prune synapses. Both astrocytes and microglia can undergo morphological and transcriptomic changes in response to infection with human immunodeficiency virus (HIV). While both astrocytes and microglia can be infected with HIV, HIV viral proteins in the local environment can interact with and activate these cells. Given that both astrocytes and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Astrocytes, similar to neurons, are heterogeneous in that they can be responsible for different shapes and functions in each area of the brain ( Miller, 2018 ; Spurgat and Tang, 2022 ). Although we investigated the function of astrocytes in the hippocampal region in this study, it is possible to study the role of astrocytes in various brain regions using cTg mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Astrocytes, similar to neurons, are heterogeneous in that they can be responsible for different shapes and functions in each area of the brain ( Miller, 2018 ; Spurgat and Tang, 2022 ). Although we investigated the function of astrocytes in the hippocampal region in this study, it is possible to study the role of astrocytes in various brain regions using cTg mice.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many subsequent studies have shown that inflammatory responses caused by disease and aging promote the activation of A1 astrocytes ( Zhang et al, 2016 ; Clarke et al, 2018 ; Xu et al, 2018 ; Qian et al, 2019 ; Zou et al, 2019 ; Li et al, 2020 ), and that A2 astrocytes are involved in the proliferation of astrocytes ( Liddelow and Barres, 2017 ). However, recent single-cell-level studies have suggested that astrocytes are heterogeneous and can be further subdivided and classified according to brain regions and stimuli-specific reactivity ( Miller, 2018 ; Wang et al, 2020 ; Hasel et al, 2021 ; Sadick et al, 2022 ; Spurgat and Tang, 2022 ). Gliogenesis occurs from late neural stem cells (NSCs) during development, but in adults, it can also occur by the proliferation of reactive astrocytes ( Wanner et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, the A1/A2 dichotomy of astrocytes is too simplified based on single-cell sequencing data but still useful as a simplified working model. Transcript analyses revealed markers common to all reactive astrocytes (e.g., GFAP [ 178 , 302 ]). The expression of complement protein C3 is a marker for inflammatory “A1” astrocytes [ 178 , 208 , 284 , 303 , 304 ].…”
Section: Primer On Astrocytes: a Network Of Guardians Of Brain Homeos...mentioning
confidence: 99%
“…Recent genomic and transcriptome studies have supported the idea that pathways associated to microglia are essential for the risk and pathogenesis of AD [ 10 ]. It’s interesting to note that recent research has shown that microglia accumulate close to amyloid-beta plaques in the AD brain and increase disease severity [ 28 , 29 , 30 ]. Therefore, the topic of this review is to offer an overview on microglia involvement in neuroinflammation and AD pathology.…”
Section: Introductionmentioning
confidence: 99%